Pippi's extraordinary ordinary day - Lindgren, Astrid, 1907-2002.; Chesworth, Michael (New York : Puffin, 2001)
When her friends Tommy and Annika have a day off from school, Pippi takes them on a far from ordinary picnic.
"The text in this book has been excerpted, with Astrid Lindgren's assistance, from two chapters in Pippi Longstocking"--P. facing t.p.
Booklist
Booklist, October 1999
4.4
K-3.
K-3
Keywords: Longstocking, Pippi (Fictitious character) -- Juvenile fiction; Picnics -- Juvenile fiction; Longstocking, Pippi (Fictitious character) -- Fiction; Picnics -- Fiction; Longstocking, Pippi (Fictional character) -- Fiction; Picnicking -- Fiction; Sweden -- Juvenile fiction; Sweden -- Fiction; Sweden -- Fiction